A bioprinted model of pregnant human uterine myometrium - Ulrich, Craig; Siddiqui, Korrina; Baldwin, Lexa K.; Hua, Weijian; Kuklok, Jacob K.; Okaikoi, Jada J.; Parker, Lauren L.; Petereit, Juli; Quilici, Dave R.; Silva, Grace M.; Sivakoses, Anutr; Wong-Fortunato, Jiavanna S.; et al. (Frontiers in Bioengineering and Biotechnology, 2025)
Despite decades of research, complications associated with dysfunctional labor are leading causes of maternal and neonatal morbidity. Currently available experimental models are not sufficient to understand the complex mechanisms underlying human labor nor to test new therapeutic approaches. We sought to develop a bioprinted tissue model of pregnant human myometrium that replicates the morphological, contractile and molecular characteristics of native pregnant human uterine myometrium as a resource to accelerate basic discovery and pharmacological testing. We have utilized primary human uterine smooth muscle cells to bioprint myometrial tissue rings containing >75% viable cells with elongated, smooth muscle morphology. Immunofluorescence confirmed expression of smooth muscle markers (caldesmon, alpha smooth muscle actin, and smooth muscle myosin), contractile-associated proteins (oxytocin receptor, prostaglandin receptors and connexin-43), and steroid hormone receptors (estrogen and progesterone receptors) characteristic of pregnant human uterine myometrium. Bioprinted tissues contracted in response to physiological agonists oxytocin (p < 0.001), prostaglandin F2α (p = 0.003), and prostaglandin E2 (p < 0.001), and relaxed in response to the nitric oxide donor S-nitrosoglutathione (p = 0.004). Further development of this model could provide an abundant and homogeneous tissue source to facilitate mechanistic studies and test agents to modulate labor.